Pelembagaan norma hukum Islam dalamperaturan daerah di Indonesia - M Sirajuddin (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2011)
The main problem of this paper is how political policy direction of local government and communityresponse to the institutionalization of norms of Islamic law in Indonesia’s local regulations. This paperuses the theoretical framework of thought which devides three Islamic groups, namely ideologicalIslamic group, moral-ethical Islamic group, and the middle way of Islam. In this paper, the direction ofgovernment policy was oriented towards the third Islamic group’s concept which institutionalizes theShari’a as a rule of formal government, but most of the only aspects of private law only, while theresponse of the majority of the community is oriented in a second Islamic group which requires theinstitutionalization of religious ethical values  which the terms of Shari’ah institutionalized in thenational legal system. Therefore, the results of surveys and responses among Indonesian thinkers moreinquire the existence of the institutionalization of norms of Islamic law than accept it. However, if anyshould be institutionalized, they would prefer the public aspects of Shari’a which should be institution-alized and implemented.